Bioindication of Urban Air Polycyclic Aromatic Hydrocarbons Using Petunia Hybrida - Benaissa, Fatima; Bendahmane, Ibrahim; Bourfis, Nassima; Aoulaiche, Oussama; Alkama, Rezak (Civil Engineering Journal, 2019)
Different ways can be used to determinate the effects of hydrocarbons on plants: the bioindication with plants is one of these methods. It consists of using sensitive plants like Petunia hybrida to evaluate the urban levels of hydrocarbon pollution. The sensitivity shows physiological and morphological modifications. In this context, this research aims to characterize the level of exposure to air pollutants resulting from anthropogenic activities in urban area of Bejaia (Algeria) by measuring the morphological impacts induced on Petunia hybrida using 11 parameters detailing the morphological development of this plant. During 7 weeks (March 23- May 11, 2017), ten monitoring stations were chosen in this city. The results showed that the most important morphological changes are directly associated with the stations closest to the main atmospheric emission zones. It is by moving away from these sources of exposure that the morphological changes observed in this bioindicating plant become less important. These results coincide with those found for particle matter concentrations including PM10 and PM2.5 which indicate that Daouadji and Aamriw stations are the most polluted sites in Bejaia. Analyzes carried out on research station located in rural area (more than 30 km from the studied city) revealed a greater general development compared to other stations.